KORELASI ANTARA KEDALAMAN SEDIMEN DI PELABUHAN BENOA DAN KONSENTRASI LOGAM BERAT Pb DAN Cu - I M. Siaka (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2008)
An investigation on the correlation between the depth of sediment in Benoa estuary and the concentration ofPb and Cu. Statistically, the sample collecting location and the sediment depth influenced the concentration of lead(Pb) and copper (Cu) significantly. The variation resources of interaction between sample collecting location and thesediment depth also showed a great influence. In general, the deeper the sediments, the lower the concentration of Pband Cu are. The average concentrations of heavy metals found in surface layer (0 cm) were 15.52 mg/kg of Pb and35.85 mg/kg of Cu. Sediment in the depth of 10 cm contained 13.49 mg/kg of Pb and 33.69 mg/kg of Cu, while thesediment in the depth of 20 cm contained 11.51 mg/kg of Pb and 32.22 mg/kg of Cu.